Production of Lactobacilli Proteinases for the Manufacture of Bioactive Peptides: Part II-Downstream Processes - Agyei, D.; Potumarthi, R.; Danquah, Michael (2013)
This chapter deals with the downstream processes of lactobacilli proteinases recovery, isolation and purification strategies. One of the most pressing bioprocess challenges in the area of production of pharmaceutical/biological materials is that of isolation and purification of the finished products. Although several isolation and purification methods exist for proteins, they must all be weighed out based on their merits and demerits. From the already established molecular and particle separations using membranes, centrifugation and phase-partitioning techniques, combinatoric techniques can be developed to ensure proteinase purification at the minimum allowed cost and high product purity. The industrial-scale use and commercialisation of lactobacilli proteinases will require the inputs of scientists, engineers, controls specialists, quality experts and economists. Further, with the important role and prospect of lactobacilli proteinases in industry, more targeted research is needed to aid in the development, purification and characterisation of robust enzymes with desired properties for wider industrial purposes.